Riwayat Pola Asuh Orang Tua pada Klien Gangguan Jiwa yang Muncul pada Usia Remaja - Suwanto (Jurnal Keperawatan Notokusumo, 2014)
Background: Teenage period is a period which is prone to stress; meanwhile teenagers are successive generation of the nation who will be leaders of the future. Parents' rearing pattern contributes to the formation of someone's personality, strong or weak, and affect someone's mentality in facing stressor. Objective: To get an overview of parents' rearing pattern to mentally disordered teenage clients at Dr. RM. Soedjarwadi Mental Hospital, Klaten. Method: The study was descriptive explorative non experimental which used quantitative approach. Data about rearing pattern of the respondent were obtained from questionnaire of Child Rearing Pattern Scale according to Yuniarti (1988). There were 31 clients who had mental disorder during teenage period (11 – 24 years of age) and were hospitalized at Dr. RM. Sodjarwadi Mental Hospital, Klaten with criteria non organic mental disorder / mental retardation, in improved health condition, able to read and write. The study was carried out from 16th November until 15th December 2006. Result: As much as 74.2% of respondents belonged to type VI rearing pattern (undistinguishable rearing pattern); 25.8% type III (democratic); 0% type I (authoritarian based on refusal); type II (authoritarian based on acceptance) or type V (permissive based on refusal). Conclusion: In average the clients who had mental disorder during teenage period (11 – 24 years of age) had type VI rearing pattern (undistinguishable).